2020
DOI: 10.21203/rs.3.rs-81763/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chip-Less and Battery-Less Subharmonic Tags for Wireless Sensing with Parametrically Enhanced Sensitivities and Dynamic Ranges

Abstract: Massive deployments of wireless sensor nodes (WSNs) that continuously detect physical, biological or chemical parameters are needed to truly benefit from the unprecedented possibilities opened by the Internet-of-Things (IoT). Just recently, new sensors with higher sensitivities have been demonstrated by leveraging advanced on-chip designs and microfabrication processes. Yet, WSNs using such sensors require energy to transmit the sensed information. Consequently, they either contain batteries that need to be pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Driven by the need of developing a new class of passive open-loop phase noise cleaners, known as parametric filters [21], [22], our group has recently investigated the stability of large-signal periodic regimes in diode-based 2:1 parametric frequency dividers (PFDs [23]), even describing a new design methodology to achieve exceptionally low parametric power thresholds (P th ) in lumped or distributed on-board PFD implementations. By further exploiting the outcomes of this investigation, we recently developed a new battery-less, chip-less and harvester-free sensor tag [24], referred to as subharmonic tag (SubHT), utilizing a 860 MHz diode-based parametric circuit made of lumped off-the-shelf components assembled on a printed substrate. Through the SubHT, we demonstrated that the proper engineering of the dynamics of diode-based parametric circuits permits to achieve extraordinarily low P th values (-18 dBm for an input frequency of 860 MHz) approaching the power threshold attainable by SoA ferritebased FSLs, even when relying on low quality factor (<80) components and on packaged diodes with junction capacitance in the pF -range.…”
Section: Introductionmentioning
confidence: 99%
“…Driven by the need of developing a new class of passive open-loop phase noise cleaners, known as parametric filters [21], [22], our group has recently investigated the stability of large-signal periodic regimes in diode-based 2:1 parametric frequency dividers (PFDs [23]), even describing a new design methodology to achieve exceptionally low parametric power thresholds (P th ) in lumped or distributed on-board PFD implementations. By further exploiting the outcomes of this investigation, we recently developed a new battery-less, chip-less and harvester-free sensor tag [24], referred to as subharmonic tag (SubHT), utilizing a 860 MHz diode-based parametric circuit made of lumped off-the-shelf components assembled on a printed substrate. Through the SubHT, we demonstrated that the proper engineering of the dynamics of diode-based parametric circuits permits to achieve extraordinarily low P th values (-18 dBm for an input frequency of 860 MHz) approaching the power threshold attainable by SoA ferritebased FSLs, even when relying on low quality factor (<80) components and on packaged diodes with junction capacitance in the pF -range.…”
Section: Introductionmentioning
confidence: 99%